Analisis Perencanaan Penjadwalan Proyek Kapal X Menggunakan Metode PERT - Valentino, Eki; Rochmoeljati, Rr. (Universitas Indraprasta PGRI Jakarta, 2024)
PT. XYZ Indonesia is a state-owned company operating in the ship industry located in Surabaya, Indonesia. PT. XYZ produces merchant ships, warships, and general engineering projects. At PT. XYZ, there is a PMO (Production Management Office) division which has a job description to organize and analyze the schedule required to complete a shipbuilding project. This research uses the PERT (Program Evaluation and Review Technique) method which is used to determine 3 durations, namely optimistic duration, pessimistic duration, and the most likely duration to occur in the machine auxiliary sub-work process on the X ship. Of course PT. XYZ also prioritizes quality and timeliness in completing his projects, so that the name of PT. Friends, you can compete on a national and international scale in the shipping industry. Therefore, this research aims to determine the most effective schedule both in terms of cost and time. The data needed in this research is the master schedule data for the X ship project. In the research that has been carried out, it was found that the processing time of the auxiliary machine is 271 Day. Thus, the conclusion obtained from this research is that schedule analysis using the PERT method has more effective results compared to predetermined planning.